Multimorbidity as an important issue among women: results of a gender difference investigation in a large population-based cross-sectional study in West Asia. Issue 5 (9th May 2017) - Alimohammadian, Masoomeh; Majidi, Azam; Yaseri, Mehdi; Ahmadi, Batoul; Islami, Farhad; Derakhshan, Mohammad; Delavari, Alireza; Amani, Mohammad; Feyz-Sani, Akbar; Poustchi, Hossein; Pourshams, Akram; Sadjadi, Amir Mahdi; et al.
Abstract : Objectives: To investigate the impact of gender on multimorbidity in northern Iran. Design: A cross-sectional analysis of the Golestan cohort data. Setting: Golestan Province, Iran. Study population: 49 946 residents (age 40–75 years) of Golestan Province, Iran. Main outcome measures: Researchers collected data related to multimorbidity, defined as co-existence of two or more chronic diseases in an individual, at the beginning of a representative cohort study which recruited its participants from 2004 to 2008. The researchers utilised simple and multiple Poisson regression models with robust variances to examine the simultaneous effects of multiple factors. Results: Women had a 25.0% prevalence of multimorbidity, whereas men had a 13.4% prevalence (p<0.001). Women of all age-groups had a higher prevalence of multimorbidity. Of note, multimorbidity began at a lower age (40–49 years) in women (17.3%) compared with men (8.6%) of the same age (p<0.001). This study identified significant interactions between gender as well as socioeconomic status, ethnicity, physical activity, marital status, education level and smoking (p<0.01). Conclusion: Prevention and control of multimorbidity requires health promotion programmes to increase public awareness about the modifiable risk factors, particularly among women.